IMPROVEMENT OF TREATMENT TECHNOLOGY OF WASTE WATERS POLLUTED WITH OIL PRODUCTS AT THE AIRTRANSPORT ENTERPRISES - Vovk О. О.; Iakovlieva А. V.; Lomotko А. V. (Science-based technologies, 2014)
World use of fuels was analyzed with taking into account ecological properties of aviation and biofuels. Impact of biofuel and aviation fuel use on the state of environment and its comparative characteristic was investigated in the article. The dependence of environmental pollution from the use of annual growth of air transport in the world was carried out. Aspects of fuel sustainability were analyzed and main standards of fuel sustainability were given. The article was excavated issue of increasing fuel efficiency. Examples of standards governing the production and use of alternative fuel in the world, such as Europe and America were given.